Групи зберiгаючих мiру гомеоморфiзмiв множини Кантора - Лавренюк, Я.В.; Некрашевич, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
We study the Bernoulli measure-preserving groups of self-homeomorphisms of spherically homogeneous trees.